Hepatitis D Viremia Among Injection Drug Users in San Francisco. (21st March 2018) - Mahale, Parag; Aka, Peter V; Chen, Xiaohua; Liu, Ping; Fram, Benjamin J; Wang, Alan S; Simenel, Scott; Tseng, Fan-Chen; Chen, Sabrina; Edlin, Brian R; Glenn, Jeffrey S; O'Brien, Thomas R
Abstract : Hepatitis D viremia was present in 35.6% of injection drug users from San Francisco who had active hepatitis B virus infection. A novel hepatitis D virus quantitative microarray antibody assay demonstrated excellent performance characteristics in this population. Abstract: People who inject drugs (PWID) are commonly exposed to hepatitis B virus (HBV) and hepatitis D virus (HDV). We evaluated the prevalence of HDV viremia among hepatitis B surface antigen (HBsAg)-positive PWID (n = 73) using a new quantitative microarray antibody capture (Q-MAC) assay, HDV western blot, and HDV RNA. HDV Q-MAC performed well in this cohort: anti-HDV, 100% sensitivity and specificity; HDV viremia, 61.5% sensitivity and 100% specificity. Hepatitis D viremia was present in 35.6% of HBsAg-positive participants and was more common in those with resolved compared to chronic hepatitis C (5.1% vs 0.6%; adjusted odds ratio, 9.80; P < .0001).